A CROSS-SECTIONAL STUDY TO ASSESS THE COMPLIANCE TO IRON FOLIC ACID TABLETS AMONG WOMEN ATTENDING ANTENATAL CLINIC - S, SIVA KEERTHIKA; BIRADAR, SANTOSH; KAMBLE, VINOD S; B, SHRINIVAS REDDY (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: As anemia is highly prevalent among pregnant women, the government of India took the initiative to start prophylactic iron folic acid tablets (IFA) to reduce its prevalence. Hence, this study was done with the objectives to assess compliance to IFA among antenatal women and to identify the associated factors. Methods: The present study was a cross-sectional study conducted among 100 women attending antenatal clinics. A pre-designed semi-structured questionnaire was used to collect the data. The data were analyzed for frequency, percentage, and Chi-square. Results: The compliance to IFA was found to be 46.15% and was significantly more in anemic pregnant women. Conclusion: The prevalence of compliance to IFA tablets was only 46.15%. Hence, counseling and awareness to be done about the importance of taking IFA tablets regularly during the antenatal period, so that compliance can be improved.